A Systematic Review of Menstrual Health and Hygiene Management (MHHM) as a Human Right for Adolescents Girls. Issue 3 (3rd July 2022) - Sood, Suruchi; Stevens, Sarah; Okumura, Maho; Hauer, Michael; Ramaiya, Astha
Abstract: Despite its relationship with several development issues and sexual health, menstrual health and hygiene management among adolescents have until recently been ignored by practitioners and researchers. This paper is a systematic review of existing literature and argues that menstrual health and hygiene management is a human rights issue. 28, 745 articles were screened, with 84 articles included in the full-text review and quality assessment. The results indicate that using a cross-cutting, human rights framework to address inadequate menstrual health and hygiene management is fundamental to promoting menstrual health and hygiene management with dignity among girls and women across the globe.